A Brief Stress Diagnostic Tool: The Short Stress Overload Scale. (December 2018) - Amirkhan, James H.
The Stress Overload Scale (SOS) has demonstrated validity in predicting pathological stress reactions; however, at 30 items, it is lengthy for some clinical applications. Here, two studies tested a 10-item SOS–Short (SOS-S). First, the SOS-S was compared with the SOS in a longitudinal community study ( n = 391), using indices of pathology as criterion measures. Results showed the SOS-S to be equivalent to the SOS in reliability and concurrent and predictive validity, although not quite as sensitive to somatic symptoms. Second, the SOS-S was compared to the 10-item Perceived Stress Scale in a cross-sectional community study ( n = 249), in which symptoms and response biases were also assessed. Results showed both measures to be susceptible to biasing, and the SOS-S to demonstrate superior validity when biases were controlled. The SOS-S appears a viable alternative to the SOS and the 10-item Perceived Stress Scale for assessing stress, and risk for sequelae, across a broad demographic spectrum.